Lockdown: A Commentary - Fusco, Gian Giacomo (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The Collins dictionary has elected lockdown as its word-of-the-yearn 2020. Defined as “the imposition of stringent restrictions on travel, social interaction and access to public spaces”, decided by governments “to mitigate the spread of COVID-19”, for Collins’ lexicographers “lockdown” took the top spot because it is a unifying experience for billions of people across the world, who have had, collectively, to play their part in combating the spread of the virus. Faced with the unknown of a brand-new virus, governments all over the world reacted in a rather familiar way, by suspending the normal flow of social life through the implementation of measures that are usually categorised as a state of exception. This article is a commentary that aims at placing the practice of lockdown (as a governmental administrative measure) in the context of the theory of state and government. To the extent that emergencies are always revelatory, this paper will argue that the state of exception – of which the lockdown is a sub-category – in displaying state’s sovereign power is exposing the radical impotence in which it is grounded, and from which it takes its ultimate meaning and function.